Antisense Oligonucleotides Targeting Angiogenic Factors as Potential Cancer Therapeutics - Bao T. Le; Prithi Raguraman; Tamer R. Kosbar; Susan Fletcher; Steve D. Wilton; Rakesh N. Veedu (Molecular Therapy: Nucleic Acids, 2019)
Cancer is one of the leading causes of death worldwide, and conventional cancer therapies such as surgery, chemotherapy, and radiotherapy do not address the underlying molecular pathologies, leading to inadequate treatment and tumor recurrence. Angiogenic factors, such as EGF, PDGF, bFGF, TGF-β, TGF-α, VEGF, endoglin, and angiopoietins, play important roles in regulating tumor development and metastasis, and they serve as potential targets for developing cancer therapeutics. Nucleic acid-based therapeutic strategies have received significant attention in the last two decades, and antisense oligonucleotide-mediated intervention is a prominent therapeutic approach for targeted manipulation of gene expression. Clinical benefits of antisense oligonucleotides have been recognized by the U.S. Food and Drug Administration, with full or conditional approval of Vitravene, Kynamro, Exondys51, and Spinraza. Herein we review the scope of antisense oligonucleotides that target angiogenic factors toward tackling solid cancers. Keywords: antisense oligonucleotides, nucleic acids, angiogenesis, antisense, modified oligonucleotides, cancer